2014
DOI: 10.1186/s12888-014-0258-z
|View full text |Cite
|
Sign up to set email alerts
|

Specialized inpatient treatment of adult anorexia nervosa: effectiveness and clinical significance of changes

Abstract: BackgroundPrevious studies have predominantly evaluated the effectiveness of inpatient treatment for anorexia nervosa at the group level. The aim of this study was to evaluate treatment outcomes at an individual level based on the clinical significance of improvement. Patients’ treatment outcomes were classified into four groups: deteriorated, unchanged, reliably improved and clinically significantly improved. Furthermore, the study set out to explore predictors of clinically significant changes in eating diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 54 publications
8
90
0
3
Order By: Relevance
“…Consistent with earlier results, we found the treatment duration to be the strongest predictor [1,4]. This result is not surprising considering the use of therapeutic weight contracts; however, it is important for ongoing discussions of reducing treatment durations.…”
Section: Tablesupporting
confidence: 81%
See 3 more Smart Citations
“…Consistent with earlier results, we found the treatment duration to be the strongest predictor [1,4]. This result is not surprising considering the use of therapeutic weight contracts; however, it is important for ongoing discussions of reducing treatment durations.…”
Section: Tablesupporting
confidence: 81%
“…Thus, early interventions targeting a young age group might be important [10]. Consistent with the work by Schlegl et al [1], patients with a higher level of education were found to be more vulnerable. Future research should address the role of academic achievement as maintaining factor.…”
Section: Tablesupporting
confidence: 78%
See 2 more Smart Citations
“…The effectiveness of therapies, especially for more severely affected patients in need of inpatient treatment, is unsatisfying (Keel & Brown, 2010). Upon discharge, only half of these patients fall into a normal weight category (Goddard et al, 2013;Schlegl et al, 2014) and only about one third exhibit clinically significant changes in their eating disorder pathologies (Schlegl et al, 2014). Consequently, there is a great need to further enhance the efficacy of interventions.…”
Section: Introductionmentioning
confidence: 99%